Endoscopic ultrasound (EUS) guided choledocoduodenostomy in a patient with irresecable pancreas cancer and biliar obstruction using a luminal apposing metal stent (LAMS). (2020) - Pinto-Carta, Renzo; Solano, Jaime; Cabrera, Luis Felipe; Sanchez, Alvaro; Moreno, Luisa; Pedraza, Mauricio
Highlights: The ERCP is the election treatment of biliary obstruction syndrome. EUS-DB is an alternative to PTBD with high technical and clinical success rate. EUS-DB is a safe and feasible procedure, providing a better quality of life to the patient. Abstract: The endoscopic retrograde cholangiopancreatography (ERCP) is the election treatment of biliary obstruction. EUS-guided biliary drainage (EUS-BD) has emerged as an alternative to PTBD with a high technical and clinical success rate, low risk of complications and a better quality of life for the patient. Case presentation we present the first case in Colombia of EUS-guided biliary drainage using luminal apposing metal stent (LAMS) in a patient with unresectable pancreatic adenocarcinoma with biliary obstruction in who ERCP was failed due to neoplastic invasion of the Vater papilla. Discussion Transhepatic biliary drainage has been the most common procedure for treatment of malignant biliary obstruction in cases which ERCP fails due to tumor infiltration of the duodenum or the Vater papilla. During the last decade the development of endoscopic ultrasound (EUS) has implied an alternative for biliary drainage in cases of failed ERCP, demonstrating advantages over Trans hepatic biliary drainage Conclusion Considering that EUS-CD is a safe procedure, with a high rate of technical and clinical success, low risk of complications.